1985
DOI: 10.3109/00365598509180256
|View full text |Cite
|
Sign up to set email alerts
|

Fine Needle Aspiration Cytology in the Diagnosis of Solid Renal and Adrenal Masses

Abstract: In the eight-year period 1977-1984, 83 renal and adrenal mass lesions which were not clearly simple cysts by ultrasonographic examination (US) were investigated by percutaneous fine needle aspiration (FNA) biopsy. Initially, biopsy was often guided by fluoroscopy, later US was by far the most commonly used modality. There were 77 renal and 6 adrenal masses; 69 lesions were malignant and 14 were benign. A positive cytological diagnosis of malignancy was given in 62 cases, a diagnostic sensitivity of 90%. One fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 18 publications
5
27
0
1
Order By: Relevance
“…Malig nancy, both primary and metastatic, was detected with nearly the same sensitivity in all organ systems of the abdomen and the chest (table 2). Similar data are reported in the recent liter ature for ultrasonically guided FNAC of the liver [2,[15][16][17], the pancreas [18][19][20], the kidneys [21,22], and the chest or gans [4,11],…”
Section: Validitysupporting
confidence: 84%
“…Malig nancy, both primary and metastatic, was detected with nearly the same sensitivity in all organ systems of the abdomen and the chest (table 2). Similar data are reported in the recent liter ature for ultrasonically guided FNAC of the liver [2,[15][16][17], the pancreas [18][19][20], the kidneys [21,22], and the chest or gans [4,11],…”
Section: Validitysupporting
confidence: 84%
“…In a systematic review, Lane et al (14) found no falsepositive results in seven series reported since 2001, with a total of 172 pathologically confi rmed lesions ( 27,(31)(32)(33)(34)(35)(36). False-positive pathologic results that have been reported in the literature (eg, misdiagnosis of an angiomyolipoma [ 63 ] or a multilocular cystic nephroma [ 64 ] as a malignancy) were predominantly reported more than 2 decades ago ( 9 ). A lack of recent reports is thought to be owing to interval advances in specimen procurement and characterization ( 9 ).…”
Section: Modeling Outcomes Of Patients Treated With Nssmentioning
confidence: 99%
“…LUTS were also improved at 1 month after the injection. However, the effect of BTX-A does not seem to be limited solely to large prostates; Chuang et al [8] reported a therapeutic effect in patients with prostate volumes of <30 mL. That study consisted of a small group of 16 men with BPH refractory to treatment with an α-blocker.…”
Section: Clinical Studiesmentioning
confidence: 99%